Paratuberculosis at European scale: an overview from 2010 to 2017 - Angela Fanelli; Domenico Buonavoglia; Carlos Martinez Carrasco Pleite; Paolo Tizzani (Veterinaria Italiana, 2020)
Mycobacterium avium subsp. paratuberculosis (MAP) is the etiological agent of paratuberculosis (PTB), a disease affecting domestic and wild ruminants. MAP may also play a zoonotic role in Crohn’s disease. Although both governments and industries are carrying out programmes to prevent and control the infection, there is a lack of harmonization across Europe. Moreover, the success of these programmes is influenced by the current lack of sensitivity of the diagnostic tests used. For these reasons, it is complex to evaluate the overall epidemiological situation of this disease. This study describes the European distribution of PTB from 2010 to 2017 using the information reported by Member Countries to the OIE. Countries were classified in three categories (‘Absent’, ‘Epizootic’, ‘Enzootic’) depending on the disease epidemiology, and the trend of countries reporting the disease presence was computed throughout the study period. A multilevel model with random slope was built for twelve countries, with complete reporting history. Most of the countries (57.44%) were classified as ‘Enzootic’. The percentage of countries reporting the disease presence slightly increased along the study period, probably due to the improvement of PTB monitoring, rather than to a deterioration of the epidemiological situation of the disease in Europe. Results of the model account for different dynamics in the number of outbreaks reported by ‘Enzootic’ and ‘Epizootic’ countries.